2019
DOI: 10.1371/journal.pone.0215407
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of cochlear implantation with chronic electric stimulation

Abstract: Objectives Cochlear implants provide an effective treatment option for those with severe hearing loss, including those with preserved low frequency hearing. However, certain issues can reduce implant efficacy including intracochlear tissue response and delayed loss of residual acoustic hearing. We describe a mouse model of cochlear implantation with chronic electric stimulation that can be used to study cochlear implant biology and related pathologies. Methods Twelve no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…1f). The smaller eABR amplitude observed with more basal electrode-stimulation is likely due to the slightly longer distance from the basal electrodes to the modulus relative to the apical electrodes, as was recently indicated in a x-ray image of a CI-implanted mouse cochlea 18 . This is also supported by a study in guinea pigs which showed that electrode position within scala tympani affects eABR threshold 19 .…”
Section: Resultsmentioning
confidence: 69%
“…1f). The smaller eABR amplitude observed with more basal electrode-stimulation is likely due to the slightly longer distance from the basal electrodes to the modulus relative to the apical electrodes, as was recently indicated in a x-ray image of a CI-implanted mouse cochlea 18 . This is also supported by a study in guinea pigs which showed that electrode position within scala tympani affects eABR threshold 19 .…”
Section: Resultsmentioning
confidence: 69%
“…The robust peri-implant cellular infiltrate in the ST of the chronically implanted groups was similar in extent to that previously published in the mouse CI model, in which the ST was occupied with fibrotic tissue and areas of neo-ossification confined to the depth of CI insertion. (Claussen et al, 2019). CX3CR1+ cells were seen to comprise a substantial element of the ST response between days 7 and 11, accounting for over 50% of the cells within the ST of some subjects.…”
Section: Discussionmentioning
confidence: 96%
“…This heterotopic tissue response is often most robust in the peri-implant region of the scala tympani (ST) forming a 'fibrous sheath' around the CI, but is sometimes seen to extend distal to the implant tip and into other scala (Linthicum et al, 2017;Nadol et al, 2014;Seyyedi & Nadol, 2014). A similar pattern of post-implantation cochlear tissue response has been seen in several animal models of cochlear implantation, including guinea pig, cat, mouse and sheep (Clark et al, 1975;Claussen et al, 2019;Kaufmann et al, 2020;O'Leary et al, 2013). Deleterious CI outcomes have been associated with the cochlear tissue response and neo-ossification, including poorer word recognition scores (Kamakura & Nadol, 2016), impedance increases with subsequent poorer battery life and decreased dynamic range (Needham et al, 2020;Wilk et al, 2016) and loss of residual acoustic hearing after cochlear implantation (Quesnel et al, 2016;Scheperle et al, 2017).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations